Genially- based interactive learning media in the sub-theme of the uniqueness In my home town - Wulandari, Madu Mitha; Safitri, Nurlinda; Purnamasari, Ratih (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2023)
This development research uses the ADDIE model (Analysis, Design, Development, Implementation , Evaluation). This research was conducted at SD Negeri Cigombong 02, Bogor Regency, and consisted of 31 students. This research was conducted in the even semester of the 2022/2023 school year. The purpose of this research is to solve the problems that fourth grade students face in the learning process. The results of the research show that the developed interactive learning media is feasible for students to use. This can be seen from the validation results carried out by media experts, linguists, and material experts showing a high percentage. Assessments from media experts showed a percentage of 94% "very feasible", linguists showed a percentage of 100% “very feasible", and material experts showed a percentage of 96% "very feasible". The results of the expert validation as a whole show a percentage of 96.6 % with the criteria of "very feasible". The limited test conducted on 31 students obtained a response of 98.8 % in the "very good" category. Based on the results of the study, it was concluded that genially- based interactive learning media is very appropriate for students to use.